GLOCALIZATION OF BALINESE LANGUAGE AS OUTDOOR SIGN IN DESA ADAT KUTA BALI - Mulyawan, I Wayan (UPI Press, 2017)
As a tourist destination, Kuta has become an international village which forces the native to use more English than Balinese in their working life. One of the most visible media of communication in Kuta is in the form of out-door sign. Out-door sign is considered to be the most effective mass media communication and the study is known as Linguistic Landscapes. The focus of this study is to investigate the glocalization of Balinese language as a medium of communication in Kuta especially, on out-door signs. The data of this study were collected by taking pictures of all out-door signs in Kuta area, such as Raya Kuta St., Kartika Plaza St., Pantai Kuta St., and Legian St.. The data were classified into two main types: commercial signs and non-commercial signs. The analysis started with identification of the language use and followed by a combination of language use in all signs. The finding shows that Balinese language is only used in 43 signs out of 1132 signs. Furthermore, from the 43 signs, there are only 22 using pure Balinese, 19 signs using Indonesian with Balinese Letters, and 2 signs using a combination of Balinese and Indonesian. The conclusion of the study is that the glocalization of Balinese language is not yet achieved; in fact, Balinese language is marginalized in Bali as out-door signs.